Cross-kingdom RNAi induced by a beneficial endophytic fungus to its host requires transitivity and amplification of silencing signals - Kellari, Loukia Maria; Dalakouras, A.; Tsiouri, O.; Vletsos, P.; Katsaouni, A.; Uslu, Veli Vural; Papadopoulou, K. K. (Plant biology, 2025)
Cross-kingdom transfer of small RNA (sRNA) molecules has been identified as a means of communication between plants and interacting microorganisms, but the mechanistic details of this sRNA-based interaction remain elusive. We have previously shown that the beneficial root-colonizing fungus Fusarium solani strain K (FsK) translocates sRNAs to its host, Nicotiana benthamiana (Nb), leading to systemic silencing of a reporter gene. Here, we investigated the mechanistic details of the endophyte-induced systemic silencing using an RNAi sensor system. We inoculated three Nb GFP expressing lines with conidia of an FsK transformant containing a transgene that targets host GFP (FsK-hpGF). The efficiency of silencing mediated by FsK-hpGF was monitored both phenotypically under ultraviolet light as well as quantitatively by RT-qPCR. sRNA sequencing was performed to evaluate the production of sRNAs targeting host GFP. Finally, bisulfite sequencing was used to assess plant GFP methylation levels. We show that the translocated fungal sRNAs induced production of secondary sRNAs, mainly of 22-24-nt in size, with the conspicuous absence of 21-nt sRNAs. Importantly, systemic silencing could not be induced in an RNA-DEPENDENT RNA POLYMERASE 6 (RDR6) CRISPR/Cas knockout background, nor in an intron-containing target gene. Overall, our data show that endophyte-induced silencing in the host requires RDR6-mediated transitivity and amplification of silencing signals. Despite being based on an artificial RNAi sensor system, our observations may reflect a more generalized and so far unexplored facet of cross-kingdom RNAi, with RDR6-based transitivity influencing the way symbionts and pathogens elicit systemic phenotypes in their host plants.